Leadership is a relationship : how to put people first in the digital world - Erwin, Michael S.; DeVoll, Willys (John Wiley & Sons, Inc., 2022)
"Discover how putting people first creates vibrant organizations and profound change In Leadership is a Relationship,Â accomplished founders and authors Michael Erwin and Willys DeVoll deliver an insightful collection of interviews with leaders who haveÂ succeeded byÂ prioritizingÂ the wellbeing of other people. The authors show howÂ you too can become a relationship-based leader and thriveÂ in our chaotic, digital world.Â ByÂ highlighting role modelsÂ from different careers, backgrounds, skill sets, and schools of thought,Â the bookÂ offersÂ readers an inspiring antidote to one of the most serious--andâ€underreported--crises of our era: the damage that digital distractions have done to our personal relationships.The book offers: Concrete strategies for combating the depersonalizationÂ ofÂ the Information Age andÂ strengthening ourÂ connections with other people Real stories ofÂ howÂ peopleÂ from Olympic champions to small-business owners have put people firstÂ Take-away tips forÂ theÂ busy reader who needsÂ quick insight or hopesÂ to use the book in a modular curriculumÂ forÂ their organization or classÂ Perfect forÂ anyone who wantsÂ toÂ leadÂ bothÂ morally and effectively,Â Leadership is a RelationshipÂ provides a concise and convincing argument thatÂ leaders whoÂ put people first have the best chance of succeeding in the twenty-first century.Â"--